A Favorita do Harém Exegese do Salmo 45 - Sousa, Fabiana de (2015)
The aim of this Master Thesis is to analyze, exegetical, the poem in 45 Psalm, especially its beauty literary, its historical context and theological dimensions. The chapters follow the poem in stanzas subdivision. Analyzing thus passage by passage, first giving attention to the Hebrew text, wherein, from the philological studies, is translated into Portuguese, in the most possible literal way. Then, studies are dedicated to stylistic elements observation, for example, the various parallels or the stanzas formation, and the latter are small literary units. Finally, the research that has been presented here focuses on the various elements of the likely historical context and theological dimensions transmitted by 45 Psalm. In particular, the study is concerned to accept the canonical exegesis principles, through parallelism observance present in Hebrew Bible, starting with the idea that the biblical texts explain themselves mutually